2008
DOI: 10.1016/j.pragma.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Complementary perspectives on metaphor: Cognitive linguistics and relevance theory

Abstract: Contemporary theories of metaphor differ in many dimensions, including the discipline they originate from (e.g., linguistics, psychology, philosophy), and whether they are developed primarily within a cognitive or pragmatic theoretical framework. This article evaluates two directions of metaphor research within linguistics, cognitive linguistics and relevance theory, which both aim to capture essential aspects of the reason for metaphor, and how people ordinarily use and understand metaphor in daily life. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(79 citation statements)
references
References 60 publications
0
68
0
11
Order By: Relevance
“…In India, fewer participants indicated that the target emotions were associated with the intended descriptors. This led us to divide the metonymies and conceptual metaphors into those that might be universal (and so might be safe to use on psychological tests) and those that appear to be culture-specific, providing interesting insights for the field of cognitive linguistics (Tendahl & Gibbs, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In India, fewer participants indicated that the target emotions were associated with the intended descriptors. This led us to divide the metonymies and conceptual metaphors into those that might be universal (and so might be safe to use on psychological tests) and those that appear to be culture-specific, providing interesting insights for the field of cognitive linguistics (Tendahl & Gibbs, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive effects are achieved when a speaker's utterance strengthens, revises or contradicts an available assumption in combination with in-hand context assumptions or by combining an in-hand context assumption with the new information to produce some new cognitive implications. Cognitive effort refers to the effort made in the mental representation of the input or the access to contextual information (Tendahl & Gibbs, 2008). Every utterance goes with itself a presumption of the best balance of cognitive effort against cognitive effect.…”
Section: Relevance Theory and Metaphormentioning
confidence: 99%
“…Relevance theoretic account of metaphor holds that metaphors are examples of "loose talk" (Sperber & Wilson, 1985/1986) instead of "an extraordinary phenomenon of language" (Wilson & Carston, 2006) and that speaking loosely is the best way to achieve optimal relevance (Tendahl & Gibbs, 2008). Metaphor interpretation requires the listener to make cognitive efforts to seek out the optimal relevance between the source and the target, or seek out similarities between the source and the target.…”
Section: Relevance Theory and Metaphormentioning
confidence: 99%
See 1 more Smart Citation
“…This general question of an integration of cognitive and communicative aspects in metaphor theory has recently become the subject of intensive theoretical and methodological discussions which focus on the relationship between CMT and specifically Relevance-theoretically (RT) oriented analyses (Carston & Wearing, 2011;Gibbs & Tendahl, 2006Sperber & Wilson, 1995Tendahl, 2009;Tendahl & Gibbs, 2008;Wilson, 2011;Wilson & Carston, 2006). This discussion can serve as a platform to sketch future perspectives in which metaphor research can contribute to CDA.…”
Section: Critical Discourse Studiesmentioning
confidence: 99%